2008
DOI: 10.1158/1078-0432.ccr-08-0941
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplex Ligand RHPS4 Potentiates the Antitumor Activity of Camptothecins in Preclinical Models of Solid Tumors

Abstract: Purpose: The formation of G-quadruplex structures at telomeric DNA sequences blocks telomerase activity, offering an original strategy to design and develop new antitumor agents. The pentacyclic acridinium salt RHPS4 is one of the most effective and selective G4 ligands able to rapidly disrupt telomere architecture, resulting in apoptosis of cancer cells. Here, we studied the therapeutic index of RHPS4 and its integration with chemotherapeutics in preclinical model of solid tumors. Experimental Design: The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 21 publications
5
62
0
Order By: Relevance
“…For instance, G4 ligands are promising compounds because they limit the proliferation of cancer cells by both short-term (telomere uncapping) and long-term (telomerase inhibition) effects. RHPS4 is one of the most selective G4 ligands with anticancer activity both as a single agent and in combination with CPTs in pre-clinical models of solid tumors (Salvati et al, 2007;Leonetti et al, 2008). This agent, behind its classical telomerase-inhibitory properties, impairs fork progression and/or telomere processing, resulting in telomere dysfunction and activation of an ATR/ATM signaling pathway (Rizzo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, G4 ligands are promising compounds because they limit the proliferation of cancer cells by both short-term (telomere uncapping) and long-term (telomerase inhibition) effects. RHPS4 is one of the most selective G4 ligands with anticancer activity both as a single agent and in combination with CPTs in pre-clinical models of solid tumors (Salvati et al, 2007;Leonetti et al, 2008). This agent, behind its classical telomerase-inhibitory properties, impairs fork progression and/or telomere processing, resulting in telomere dysfunction and activation of an ATR/ATM signaling pathway (Rizzo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that the combination of RHPS4 with CPT also has a strong synergistic interaction in vitro on colon cancer lines and produced marked antitumor activity on xenografts (Leonetti et al, 2008). Unfortunately, this combination failed to cure animals as no complete remissions were reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations